Exploring the Values of Patience and Optimism in Islamic Character Education: A Content Analysis of La Tahzan by Aidh Al-Qarni - Aang Kunaifi; Imam Wahyono; Vina Rohmatul Ummah; Ahmad Aziz Fanani (Journal of Educational Management Research, 2026)
This study aims to explore the values of patience and optimism as fundamental dimensions of Islamic character education embedded in La Tahzan by Aidh Al-Qarni. A qualitative library research approach was employed, using La Tahzan as the primary data source and relevant books and scholarly articles as secondary sources. Data were collected through documentation and analyzed using qualitative content analysis, involving data identification, coding, categorization, interpretation, and conclusion drawing. The findings reveal that the book consistently promotes two core character values. Patience is reflected in perseverance in worship, self-restraint from sinful behavior, and steadfastness in facing adversity with sincerity and trust in Allah. Meanwhile, optimism is expressed through positive expectations for the future, confidence in Allah’s mercy and guidance, and persistence in striving despite challenges and failures. These values are presented as complementary principles that strengthen resilience, self-discipline, and spiritual commitment. The study implies that La Tahzan represents a valuable source of Islamic character education and may serve as a reference for integrating patience and optimism into character development programs and educational practices aimed at fostering resilient and morally grounded learners.